Low cardiac dose and neutrophil-to-lymphocyte ratio predict overall survival in inoperable esophageal squamous cell cancer patients after chemoradiotherapy - Yu-Chieh Ho (Nature Portfolio, 2021)
Abstract We aimed to determine the prognostic significance of cardiac dose and hematological immunity parameters in esophageal cancer patients after concurrent chemoradiotherapy (CCRT). During 2010–2015, we identified 101 newly diagnosed esophageal squamous cell cancer patients who had completed definitive CCRT. Patients' clinical, dosimetric, and hematological data, including absolute neutrophil count, absolute lymphocyte count, and neutrophil-to-lymphocyte ratio (NLR), at baseline, during, and post-CCRT were analyzed. Cox proportional hazards were calculated to identify potential risk factors for overall survival (OS). Median OS was 13 months (95% confidence interval [CI]: 10.38–15.63). Univariate analysis revealed that male sex, poor performance status, advanced nodal stage, higher percentage of heart receiving 10 Gy (heart V10), and higher NLR (baseline and follow-up) were significantly associated with worse OS. In multivariate analysis, performance status (ECOG 0 & 1 vs. 2; hazard ratio [HR] 3.12, 95% CI 1.30–7.48), heart V10 (> 84% vs. ≤ 84%; HR 2.24, 95% CI 1.26–3.95), baseline NLR (> 3.56 vs. ≤ 3.56; HR 2.36, 95% CI 1.39–4.00), and follow-up NLR (> 7.4 vs. ≤ 7.4; HR 1.95, 95% CI 1.12–3.41) correlated with worse OS. Volume of low cardiac dose and NLR (baseline and follow-up) were associated with worse patient survival.